Karakteristik kasus otitis eksterna di RSUP Sanglah Denpasar periode April 2015-April 2016 - N.P Mirah Ayunda Kartika Wulandari; I Made Sudipta (Intisari Sains Medis, 2020)
Background: External Otitis (OE) is one of the most common cases in ENT. There are an estimated 8.1 visits with an OE diagnosis per 1,000 annually. The low understanding of the community about OE caused the cases to become frequent. This study aims to increase public understanding of OE by knowing the characteristics of OE in Sanglah Hospital.Methods: A study with descriptive cross sectional method. Samples were taken from Sanglah Hospital's medical record data on period 2015-2016 with total sampling method.Results: A total of 84 samples were successfully analyzed, and found: OE was most common in the 15-49 years age group (55.9%). Gender dominating is female (52.4%). The most clinical symptoms of OE patients were ear pain (67.9%), followed by ear discharge (55.9%), ear that felt full (22.6%), itchiness (20.2%), ringing (21.4%), hearing loss (15.5%), and accompanied (4.8%). The most frequent cause of OE is due to trauma (58.3%), followed by fungi or bacterial infection (20.3%), combined causes (11.9%), and the least caused by systemic disease (9.5%).Conclusions: The OE case at Sanglah Hospital is most commonly found in the female population, age group 15-49 years, with the most common symptom of earache and caused by mechanical trauma.Â Latar Belakang: Otitis Eksternal (OE) merupakan salah satu kasus yang sering ditemukan dalam bidang THT. Diperkirakan terdapat 8.1 kunjungan dengan diagnosis OE per 1.000 per tahunnya. Rendahnya pemahaman masyarakat mengenai OE menyebabkan kasus ini menjadi sering terjadi. Studi ini bertujuan untuk meningkatkan pemahaman masyarakat mengenai OE dengan mengetahui gambaran kejadian OE di RSUP Sanglah.Metode: Sebuah studi dengan metode deskriptif potong lintang. Sampel diambil dari data rekam medis RSUP Sanglah pada periode 2015-2016 dengan metode total sampling .Hasil: Sebanyak 84 sampel berhasil di analisis, dan ditemukan: OE paling sering terjadi pada kelompok umur 15-49 tahun, (55,9%). Jenis kelamin yang mendominasi adalah perempuan (52,4%). Gejala klinis penderita OE terbanyak adalah nyeri telinga (67,9%), diikuti berair atau keluar cairan dari telinga (55,9%), terasa penuh (22,6%), rasa gatal (20,2%), berdenging (21,4%), gangguan pendengaran (15,5%), dan yang disertai (4,8%). Penyebab OE terbanyak adalah karena trauma (58,3%), diikuti karena jamur atau bakteri (20,3%), penyebab gabungan (11,9%), dan paling sedikit disebabkan oleh penyakit sistemis (9,5%).Simpulan: Kasus OE di RSUP Sanglah paling sering ditemui pada populasi wanita, kelompok umur 15-49 tahun, dengan gejala tersering berupa nyeri telinga dan disebabkan oleh trauma mekanis. Â